Characteristic Differences between Freeze-dried Tenogenic Secretomes and Freeze-dried Crude Secretomes of Mesenchymal Stem Cells under Hypoxic Conditions - Agus Kresnadi; Mouli Edward; Gilson Khang; Heri Suroto (Wolters Kluwer - Medknow Publications, 2024)
Introduction: Tendons that are crucial for movement are struggling with self-healing. Regenerative medicine has been using mesenchymal stem cells (MSCs) and their secretomes, and it offers promise. These secretomes, rich in growth factors, aid tissue healing. Tenogenic secretomes target tendon-specific healing, while crude ones provide a broader view of MSC signaling. The study aims to enhance targeted interventions in tendon regeneration and improve the quality of life for those with tendon-related issues. Methods: This laboratory study compares freeze-dried tenogenic and crude secretomes of MSCs under hypoxic conditions for regenerative potential. Stem cells from adipose tissue undergo isolation, culture, and multiplication then treated in hypoxic conditions. Characterization, Interleukin-6 (IL-6) and Interleukin-10 (IL-10) analysis with enzyme-linked immunosorbent assay (ELISA) follow. The results, including organoleptic, pH, and scanning electron microscope assessments, were presented descriptively. Statistical analysis will enhance understanding. Results: Physical characteristics (odor, color, and pH) are similar in both groups. Tenogenic secretome has a more concave surface, potentially aiding cell migration compared to the crude secretome. There were significant differences in cytokine levels (P = 0.001). IL-6 levels expressed from tenogenic secretome were 10.2 ± 2.432 pg/mL compared to the crude one which 18.3 ± 3.175 pg/mL. Levels of IL-10 expressed from tenogenic and crude secretomes were 309.2 ± 50.973 pg/mL and 200.1 ± 32.030, respectively. Conclusion: The tenogenic secretome and crude secretome exhibit no differences in physical characteristics but differ in surface morphology. The concave surface of the tenogenic secretome facilitates cell migration more than the crude secretome. Under hypoxic conditions, the tenogenic secretome shows lower pro-inflammatory (IL-6) and higher anti-inflammatory (IL-10) effects than the crude secretome.